INDIVIDUAL APPROACH IMPLEMENTATION IN THE PROCESS OF PRACTICAL WORK OF HIGH SCHOOL STUDENTS OF TECHNOLOGICAL SPECIALTY - Uruskyi, Andriy V. (Educological discourse, 2015)
The possibilities of applying individual approach at technological classes during high school students’ practical work have been reviewed. An approximate list of products for carpentry and turning operations have been offered. The peculiarities of individual approach implementation to students in the process of self-selection of work facility, technical documentation, product improvement, its decoration have been revealed. The algorithm of individual students’ characteristics consideration during the process of product manufacture has been shown.